Analyzing Consumer Motivations and Behaviors Towards Upcycled Food from an Environmental Sustainability Perspective - Wen-Shin Huang; Tzung-You Tsai; Kung-Ling Lai; Han-Shen Chen (Agriculture)
Green energy consumption is a pressing global environmental issue that necessitates the optimization of food system circularity to effectively utilize natural resources. The rise of food technology has introduced upcycled food as a promising solution for reducing food waste and promoting sustainability. Despite its potential, research on consumer attitudes toward upcycled food remains scarce. This study investigates the role of upcycled food in shaping Taiwanese consumers’ behaviors in response to environmental challenges, utilizing the value–attitude–behavior (VAB) model with a focus on variables such as “product novelty”, “green perceived value”, and “ethical consumption”. Using convenience sampling, 297 valid responses were collected, achieving a response rate of 91.1%. Findings indicate that health values significantly enhance positive attitudes toward upcycled food, which in turn positively influences behavioral intentions. However, neither green perceived value nor product novelty significantly affected these intentions. These insights highlight the importance of prioritizing health values, consumer attitudes, and ethical consumption in marketing strategies for upcycled food to engage potential consumers and promote environmental sustainability. This study addresses a critical gap in the existing literature and suggests a strategic direction for the food industry.